Ilyenkov's ideal: Can we bank on it?. Issue 3 (23rd February 2022) - Ward, Mike
Abstract: Education for Sustainable Development (ESD) supports processes of change in complex socio-ecological systems. Where and how this change takes place are important considerations as we seek to enhance our capacity to challenge existing systems and thus produce and reproduce our life activities in more sustainable ways. This paper considers the possibilities for change in a system as deeply embedded in our social and material existence as capitalism. It rejects the notion that there is no alternative and considers the implications of Evald Ilyenkov's exploration and development of the Dialectic of the Ideal as the basis for change. I reflect on Ilyenkov's work in relation to a recent national (South African) study into the potential for creating a more sustainable banking sector and the associated education and skills development requirements. The individualising response to sustainability challenges is rejected through the opening up of a more nuanced understanding of the role of contradictions evident in the reciprocal movement and mutual transformations between society and the material structures, both natural and built, within which society exists.